2010
DOI: 10.1177/112067211002000111
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Implantation of the Acri.LISA Bifocal Intraocular Lens in Myopic Eyes

Abstract: Bilateral implantation of the Acri.LISA 366D in high myopic eyes provides a satisfactory full range of vision comparable to that obtained in low-moderate myopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
3
10
2
Order By: Relevance
“…In the present study, both corrected and uncorrected VA for far and near vision were comparable to those previously reported after implantation of earlier bifocal IOLs (18,26,27). This is consistent with findings in a recent comparative study by Mojzis et al (22).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, both corrected and uncorrected VA for far and near vision were comparable to those previously reported after implantation of earlier bifocal IOLs (18,26,27). This is consistent with findings in a recent comparative study by Mojzis et al (22).…”
Section: Discussionsupporting
confidence: 93%
“…Nontoric AT Lisa multifocal IOL implantation has been evaluated in several studies. [18][19][20][21] This IOL has the same platform as the AT Lisa toric IOL. These studies showed postoperative monocular UDVA rates ranging from 0.07 to 0.23 logMAR.…”
Section: Complicationsmentioning
confidence: 99%
“…A similar study was carried out by Fernández-Vega and co-workers 47 assessing visual quality after bilateral implantation of Acri.LISA 366 IOLs in patients with high and low-moderate myopia. The parameters studied included distance, near and intermediate visual acuity, and distance contrast sensitivity under photopic and mesopic conditions after bilateral implantation of Acri.LISA 366D in 106 eyes with low-moderate myopia and in 198 eyes with high myopia.…”
Section: High Ametropiamentioning
confidence: 94%
“…13 Montés-Micó and coauthors 13 reported that patients with multifocal IOLs had worse CSF under dim conditions. Studies evaluating the CSF after hybrid multifocal IOL implants 20,26,29,30,32,35,38,39,43,[46][47][48][49][50] also found a reduction in contrast sensitivity when the luminance level was reduced, particularly for higher spatial frequencies. This trend agrees with classic data on the effect of the luminance level on contrast sensitivity.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation